(untitled) (Ukrainian Journal of Ophthalmology, 2025)
From year to year, there has been an increase in the number of children with poor reading skills. The paper focuses on a neuropsychological approach to assessing reading learning difficulties in visually impaired children. Purpose: To examine the impact of neuropsychological characteristics on reading learning difficulties in visually impaired children. Material and Methods: The study sample included 72 children aged 8-12 years; of these, 36 had a vision impairment. We used a battery of neuropsychological tests proposed by Luria and adapted for children by Glozman. Statistical analysis was conducted using IBM SPSS Statistics 23 software. Results: There was a significant difference (p < 0.05) in neuropsychological test results between the experimental group and controls. The neuropsychological symptom complex (cluster) for visually impaired children comprises certain markers of regulation and control like Difficulties in Memorizing a Series of Elements, Difficulties in Retaining Semantic Elements of a Text, Immaturity of Holistic Reading, Slow Reading, Impossibility to Make a Program for an Arithmetic Problem, Difficulties in Naming the Found Category, and Situational Generalization. Conclusion: It was found that the degree of the maturity of neuropsychological characteristics (regulation mechanisms) in the domains of motor and intellectual functioning has an effect on learning difficulties in reading in visually impaired children. Understanding the neuropsychological mechanisms of reading disorders in visually impaired children has a key value for neuropsychological differential diagnosis with subsequent correct identification of targets for neuropsychological correction.